EUROPEAN OAK’S GROWTH RINGS PROPERTIES: DENSITY DISTRIBUTION AND THERMAL BEHAVIOR ANALYSIS OF EARLY – AND LATEWOOD - Hamada, Joël; Pétrissans, Anélie; Mothe, Frédéric; Gérardin, Philippe; Pétrissans, Mathieu (Innovation in Woodworking Industry and Engineering design, 2015)
Last decades wood is promoted as building material. Unprotected wood exposed to outdoor conditions undergoes a variety of degradation induced essentially by fungi attacks. Heat treatment of wood by mild pyrolysis (180°C